Pemberdayaan Ibu Rumah Tangga di Desa Rabauh melalui Digitalisasi dan Branding Produk Olahan Singkong - Komang; Joy Angel Aria Suma; Rensa; Aini; Indah Laura Nafrati Lova; Oktamie Natalia; Rizqi Fatwandiki Ramadhani; Mei Laura Beautrik Simanungkalit; Yohanes Indra Yudha; Oktafya Syahputri; Hanna Sinaga; Erni Dwi Puji Setyowati; Imelda Simanjuntak (Jurnal Abdikaryasakti, 2025)
The low level of cassava processing in rural areas of Central Kalimantan has led to untapped local economic potential. This community service activity aims to empower housewives in Rabauh Village by enhancing their skills in production, packaging, branding, and digital marketing of cassava-based processed products. The program was implemented by students of the University of Palangka Raya during the Regular Community Service (KKN) Period I in 2025 (July 16–August 18, 2025), involving 25 participants, most of whom were active housewives engaged in the Family Welfare Empowerment (PKK) program. A Participatory Action Research (PAR) approach was applied to ensure participants’ active involvement in every stage of the activity, from needs identification and training to evaluation. The training focused on producing hygienic cassava chips with various flavors, creating simple product labels and packaging, and promoting products through social media. The results showed that 84% of participants improved their technical production skills, and 88% experienced socio-economic benefits through increased income and self-confidence in entrepreneurship. In addition to producing signature products such as “Spicy Sweet Cassava Chips with Kaffir Lime Leaves,” the activity also increased participants’ awareness of the importance of digitalization for micro-enterprises. Overall, the SIBER program made a tangible contribution to enhancing rural women’s economic capacity, fostering local food innovation, and serving as a sustainable empowerment model based on regional food potential in Central Kalimantan.